Analysis of the Internal Control System for Cash Receipts at the Tirtanadi Waterworks Company, Diski Medan Branch - Hendra Saputra; Ayu Kurnia Sari (CV Raskha Media Group, 2025)
This study aims to analyse the effectiveness of the internal control system for cash receipts at the Tirtanadi Waterworks Company, Diski Medan Branch. Cash receipt activities play a crucial role in supporting the company’s operational sustainability, making an adequate internal control system essential to ensure the reliability of financial information and the safeguarding of company assets. The research employs a descriptive qualitative method by collecting data through observations, interviews, and documentation related to procedures for receiving cash from customers. The results of the study indicate that the internal control system for cash receipts at the Diski Medan Branch is generally well-implemented, as evidenced by the separation of duties, the use of authorisation procedures, and the existence of routine supervision. However, several weaknesses were identified, such as the lack of periodic evaluations, limited use of digital systems, and insufficient documentation for certain transactions, which may create opportunities for human error or fraud. Strengthening these areas is necessary to enhance the reliability and transparency of financial processes. Overall, the study concludes that while the internal control system for cash receipts is functioning adequately, improvements are still required to ensure optimal financial control and minimise risks. This research is expected to contribute to the development of better cash management practices within the company